2023
DOI: 10.1038/s41594-023-01120-6
|View full text |Cite
|
Sign up to set email alerts
|

EMC rectifies the topology of multipass membrane proteins

Haoxi Wu,
Luka Smalinskaitė,
Ramanujan S. Hegde

Abstract: Most eukaryotic multipass membrane proteins are inserted into the membrane of the endoplasmic reticulum. Their transmembrane domains (TMDs) are thought to be inserted co-translationally as they emerge from a membrane-bound ribosome. Here we find that TMDs near the carboxyl terminus of mammalian multipass proteins are inserted post-translationally by the endoplasmic reticulum membrane protein complex (EMC). Site-specific crosslinking shows that the EMC’s cytosol-facing hydrophilic vestibule is adjacent to a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…S. cerevisiae has no annotated TRAP genes, and indeed it has been suggested that most fungi lack TRAP 104 . However, we find that S. cerevisiae contains a previously unidentified gene for TRAPα (Irc22, HHpred E = 10 -35 ). This suggests TRAP’s prevalence in fungi has been underestimated.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…S. cerevisiae has no annotated TRAP genes, and indeed it has been suggested that most fungi lack TRAP 104 . However, we find that S. cerevisiae contains a previously unidentified gene for TRAPα (Irc22, HHpred E = 10 -35 ). This suggests TRAP’s prevalence in fungi has been underestimated.…”
Section: Resultsmentioning
confidence: 71%
“…At least one main function of EMC is to facilitate insertion of TMDs close to the N- or C-terminus. This includes post-translational insertion of tail-anchored proteins 34 , post-translational insertion of the final TMD of some multipass membrane proteins 35 , and co-translational insertion of SAs in the N exo topology (N-terminus facing the exoplasmic side of the membrane) 23,36 . This insertase function is thought to involve its core EMC3 subunit 24,35,3740 , which is a member of the Oxa1 family of insertases 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap between the vestibule and the intramembrane sulcus provides a possible pathway for matrix outflow from EMC. These findings shed light on how EMC facilitates energy‐independent membrane insertion of TMDs, elucidating why only short‐lumen domains are transported by EMC and supporting the proposed companion function model of EMC 41,42 . Next, we will focus on cryo‐electron microscopy (cryo‐EM) structures of human EMC.…”
Section: Structure Of Emcmentioning
confidence: 79%
“…These findings shed light on how EMC facilitates energyindependent membrane insertion of TMDs, elucidating why only short-lumen domains are transported by EMC and supporting the proposed companion function model of EMC. 41,42 Next, we will focus on cryo-electron microscopy (cryo-EM) structures of human EMC. When it was first discovered, the structure of EMC was not clear, but research teams continued to contribute to the analysis of the EMC structure, and the precise structure of EMC was outlined step by step (Table 2).…”
Section: Cryo-em Structures Of Human Emcmentioning
confidence: 99%